2007
DOI: 10.1007/s10544-007-9064-4
|View full text |Cite
|
Sign up to set email alerts
|

Low noise bipolar photodiode array protein chip based on on-chip bioassay for the detection of E. coli O157:H7

Abstract: A bipolar photodiode array (PDA) protein chip is presented for the detection of E. coli O157:H7. Through unique design of the bipolar PDA microchip, the device was able to detect E. coli O157:H7 directly on the surface of the bipolar PDA. The bipolar PDA microchip maintained low noise level in the entire process of on-chip protein assay and demonstrated high performance of analog signal processing. At every reaction step of the on-chip bioassay, stability of wet photodiode detection elements was confirmed by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…It was also suggested that the second mode reflection minima and maxima produced by the ani-reflection siliceous layer attributed to the local extrema (Fiaccabrino et al 1998) in the overall spectral characteristics of a photodiode array optimized for a peak wavelength value centered around 620 nm. Fluorescence emissions of fluorescein and alexa fluor 647 measured using the constructed bipolar PDA microchip as a photodetector further evidenced the wavelength dependent optical sensitivity of silicon matrix in the bipolar PDA (Kim et al 2007). Compared to fluorescein (lem=520 nm), alexa fluor 647 (lem=668 nm) provided almost 4-fold higher signal at the identical concentration.…”
Section: Photoresponse Of the Pda Chipmentioning
confidence: 82%
See 3 more Smart Citations
“…It was also suggested that the second mode reflection minima and maxima produced by the ani-reflection siliceous layer attributed to the local extrema (Fiaccabrino et al 1998) in the overall spectral characteristics of a photodiode array optimized for a peak wavelength value centered around 620 nm. Fluorescence emissions of fluorescein and alexa fluor 647 measured using the constructed bipolar PDA microchip as a photodetector further evidenced the wavelength dependent optical sensitivity of silicon matrix in the bipolar PDA (Kim et al 2007). Compared to fluorescein (lem=520 nm), alexa fluor 647 (lem=668 nm) provided almost 4-fold higher signal at the identical concentration.…”
Section: Photoresponse Of the Pda Chipmentioning
confidence: 82%
“…It was shown in our previous study (Kim et al, 2007) that the photodiode has photoresponse over a wide range of wavelength, from visible to near-IR (400-1,100 nm). The wavelength dependent optical sensitivity is highly influenced by concentration and structure of silicon matrix.…”
Section: Photoresponse Of the Pda Chipmentioning
confidence: 84%
See 2 more Smart Citations
“…10,11 Micro-and nanosized arrays prepared by the superior techniques of lithography and patterning are useful for the screening of trace amounts of analytes. 12,13 To produce the array for biosensing, a protein array on a solid surface has the requirement of selective protein interaction [14][15][16] and high spatial resolution.…”
Section: Introductionmentioning
confidence: 99%